A Secure E-Voting Web-Based System utilizing Bcrypt hashing, Email One-Time Password and Email Verification for Politeknik METrO Tasek Gelugor - Robert, Nethaneal; Abd Warif, Nor Bakiah (Applied Information Technology And Computer Science, 2024)
This project aims to develop a Secure E-Voting Web-Based System for Politeknik METrO Tasek Gelugor using the Bcrypt hash function, email one-time password for password recovery, and email verification. The current manual voting method lacks secrecy, authentication, and integrity, compromising effectiveness. The new system seeks to improve security and accessibility, ensuring voter confidentiality and process integrity. Utilizing the Agile methodology for iterative development and feedback, the system includes email verification, password authentication, Bcrypt hashing, and email-based one-time passwords. The expected outcome is a secure, effective system promoting democratic participation. The project underscores the potential for transforming electronic voting systems, enhancing voter engagement, and upholding democratic values at Politeknik METrO Tasek Gelugor.